Left Atrial Septal Pouch in Cryptogenic Stroke - Wong, Jonathan M.; Lombardo, Dawn M.; Barseghian, Ailin; Dhoot, Jashdeep; Hundal, Harkawal s.; Salcedo, Jonathan; Paganini-Hill, Annlia; Wong, Nathan D.; Fisher, Mark (Frontiers in Neurology, 2015)
Background: The left atrial septal pouch (LASP), an anatomic variant of the interatrial septum, has uncertain clinical significance. We examined the association between LASP and ischemic stroke subtypes in patients undergoing transesophageal echocardiography (TEE). Methods: We determined the prevalence of LASP among consecutive patients who underwent TEE at our institution. Patients identified with ischemic strokes were further evaluated for stroke subtype using standard and modified criteria from the Trial of Org 10172 in Acute Stroke Treatment (TOAST). We compared the prevalence of LASP in ischemic stroke, cryptogenic stroke, and non-stroke patients using prevalence ratios (PR). Results: The mean age of all 212 patients (including stroke and non-stroke patients) was 57 years. The overall prevalence of LASP was 17% (n=35). Of the 75 patients who were worked-up for stroke at our institution during study period, we classified 31 as cryptogenic using standard TOAST criteria. The prevalence of LASP among cryptogenic stroke patients (using standard and modified TOAST criteria) was increased compared to the prevalence among other ischemic stroke patients (26% vs. 9%, p=0.06; PR=1.8, 95% CI=1.1-3.1 and 30% vs. 10%, p=0.04; PR=2.2, 95% CI=1.2-4.1, respectively). Conclusions: In this population of relatively young patients, prevalence of LASP was increased in cryptogenic stroke compared to stroke patients of other subtypes. These findings suggest LASP is associated with cryptogenic stroke, which should be verified by future large-scale studies.